Pemanfaatan Susu Kedelai sebagai Bahan Pensubtitusi Susu Sapi dalam Pembuatan Es Krim Labu Kuning - Prihatin, Neneng; Hamzah, Faizah; Yusmarini, Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aimed to obtain an appropriate formulation between cow's milk and soy milk in making of pumpkin ice cream. This experiment was conducted experimentally using a random design with five treatments and three replications and followed by DNMRT at 5% level. The treatment in this study were SSSK1 (100% cow’s milk), SSSK2 (25 % soy milk : 75% cow’s milk), SSSK3 (50% soy milk: 50% cow’s milk), SSSK4 (25% soy milk: 75% cow’s milk), SSSK5 (100% soy milk). The parametersobserved were overrun, melting time, protein content, fat content, total solids, descriptive and hedonic sensory evaluation (colour, flavor, texture, and taste). The results of the study showed that the best treatment was the treatment of SSSK2 (25% soy milk: 75% cow’s milk) with the result of 20.56% overrum, 18.34 minutes melting time, 3.21% protein content, 3.08% fat content and 28.20% total solids. The results of a hedonic assessment of the likes with the descriptive color is slightly yellow, flavored cow's milk, rather soft texture. Keywords: Ice cream, pumpkin, soymilk